Kualitas Pelayanan Perizinan dalam Meningkatkan Kepuasan Pelaku Usaha UMKM Di Pulo Gadung Jakarta Timur - Agung Edi Rustanto; Donny Oktavian Syah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
In the business entities run by MSMEs (Micro Small Medium Enterprises), fulfilling the needs of consumers is a key that must be fulfilled. Business development by MSMEs in Pulo Gadung is relatively good, so it will be even better if MSME licensing management can be carried out thoroughly. The population of this study has not known yet with certainty because there are several MSMEs that are less affordable by researchers and in determining the sample, namely through the Lemeshow formula, it is determined that the minimum sample size is 96 respondents. The research implemented a quantitative approach, with data collection techniques using questionnaires, and using a simple regression correlation coefficient. The effect of service quality (X) on business actor satisfaction (Y), based on the results of the T-test in this study, the test results show that the independent variable, namely service quality, has a positive and significant influence on satisfaction. Thus, it can be stated that the service quality hypothesis has a significant influence on business actor satisfaction. Moreover, t-test indicates that the quality of service has a positive and significant influence on the satisfaction of business actors. The results of this study indicate that service quality has a significant effect on the satisfaction of MSME business actors.